2016
DOI: 10.3389/fnagi.2016.00004
|View full text |Cite
|
Sign up to set email alerts
|

Limited Effect of Dopaminergic Medication on Straight Walking and Turning in Early-to-Moderate Parkinson’s Disease during Single and Dual Tasking

Abstract: BackgroundIn Parkinson’s disease (PD), the effects of dopaminergic medication on straight walking and turning were mainly investigated under single tasking (ST) conditions. However, multitasking situations are considered more daily relevant.MethodsThirty-nine early-to-moderate PD patients performed the following standardized ST and dual tasks as fast as possible for 1 min during On- and Off-medication while wearing inertial sensors: straight walking and turning, checking boxes, and subtracting serial 7s. Quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…In accordance with the findings in this study, previous behavioural research has shown that the administration of dopaminergic replacement therapy often improves step time variability in Parkinson's disease patients (Hausdorff, et al, 2003a;Lord et al, 2011;Rochester et al, 2011;Bryant et al, 2016). Furthermore, impairments in dual-task walking are also often improved by optimal dopaminergic replacement therapy (Camicioli et al, 1998;Lord et al, 2011;Elshehabi et al, 2016).…”
Section: Approximate Position Figuresupporting
confidence: 91%
“…In accordance with the findings in this study, previous behavioural research has shown that the administration of dopaminergic replacement therapy often improves step time variability in Parkinson's disease patients (Hausdorff, et al, 2003a;Lord et al, 2011;Rochester et al, 2011;Bryant et al, 2016). Furthermore, impairments in dual-task walking are also often improved by optimal dopaminergic replacement therapy (Camicioli et al, 1998;Lord et al, 2011;Elshehabi et al, 2016).…”
Section: Approximate Position Figuresupporting
confidence: 91%
“…Patients in the lab-based assessment were measured during their medication ON phase, i.e., during the study participant’s perception of having a good “on” phase after regular intake of medication ( Elshehabi et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Comparable to Ref. (19), medication OFF was defined as overnight withdrawal from dopaminergic medication, and medication ON as the study participant’s perception of having a “Good On Phase,” after regular intake of medication. The assessment consisted of daily activity-like procedures, such as walking in the rooms and corridors of the lab environment without restriction, opening and closing doors, climbing stairs, performing transfers such as sit-to-stand, sit-to-walk, stand-to-sit and walk-to-sit, brushing teeth, making coffee, drinking a cup of tea, and ironing (18).…”
Section: Methodsmentioning
confidence: 99%